The EPICC Family of Anti-Inflammatory Peptides: Next Generation Peptides, Additional Mechanisms of Action, and In Vivo and Ex Vivo Efficacy - Krishna, Neel K.; Cunnion, Kenji M.; Parker, Grace A. (Frontiers in Immunology, 2022)
The EPICC peptides are a family of peptides that have been developed from the sequence of the capsid protein of human astrovirus type 1 and previously shown to inhibit the classical and lectin pathways of complement. The EPICC peptides have been further optimized to increase aqueous solubility and identify additional mechanisms of action. Our laboratory has developed the lead EPICC molecule, PA-dPEG24 (also known as RLS-0071), which is composed of a 15 amino acid peptide with a C-terminal monodisperse 24-mer PEGylated moiety. RLS-0071 has been demonstrated to possess other mechanisms of action in addition to complement blockade that include the inhibition of neutrophil-driven myeloperoxidase (MPO) activity, inhibition of neutrophil extracellular trap (NET) formation as well as intrinsic antioxidant activity mediated by vicinal cysteine residues contained within the peptide sequence. RLS-0071 has been tested in various ex vivo and in vivo systems and has shown promise for the treatment of both immune-mediated hematological diseases where alterations in the classical complement pathway plays an important pathogenic role as well as in models of tissue-based diseases such as acute lung injury and hypoxic ischemic encephalopathy driven by both complement and neutrophil-mediated pathways (i.e., MPO activity and NET formation). Next generation EPICC peptides containing a sarcosine residue substitution in various positions within the peptide sequence possess aqueous solubility in the absence of PEGylation and demonstrate enhanced complement and neutrophil inhibitory activity compared to RLS-0071. This review details the development of the EPICC peptides, elucidation of their dual-acting complement and neutrophil inhibitory activities and efficacy in ex vivo systems using human clinical specimens and in vivo efficacy in animal disease models.